Rehabilitation of military servicemen: existential approach - Naumenko, Anastasia (Psychological Prospects Journal, 2025)
Purpose. The article aims to highlight the current problem of psychological rehabilitation of military personnel who have been exposed to psychotraumatic factors in the combat zone. Methods. The study employed the following methods of scientific and theoretical investigation of the problem to achieve its purpose: analysis, synthesis, comparison, generalization, abstraction, and systematization of scientific research on the issues of servicemen’s rehabilitation. Results. An analysis of modern scientific approaches to psychological rehabilitation was conducted, including military-psychological, medical, general psychological, and socio-psychological approaches. The necessity of applying the existential approach, particularly Dasein-analysis, which is based on the phenomenological study of "being-in-the-world" and allows for the exploration of each serviceman’s unique experience, the restoration of connection with their own body and sexuality, and helps to comprehend the past, present, and future, is substantiated. Dasein-analytic psychotherapy is considered through its three fields of analysis (Umwelt, Mitwelt, Eigenwelt), and the effectiveness of the deconstruction method of the client’s "ideal world" and the formation of a new, more functional self-image is analyzed. Special attention is paid to considering existential aspects such as the awareness of mortality, freedom, isolation, and meaninglessness, as well as sexuality, as important elements of rehabilitation. Understanding sexuality as an embodied perceptive experience can help servicemen restore healthy sexual relationships. Conclusions. War, as an extreme situation, causes deep psychological traumas that manifest as post-traumatic stress disorder, depression, anxiety, and loss of meaning in life. Traditional approaches to rehabilitation, which focus on adaptation to social norms, prove insufficient as they ignore the deep existential questions and the impact of trauma on sexuality. Dasein-analysis is a promising method for working with servicemen, which not only facilitates overcoming psychological traumas but also restores the meaning of life, freedom, and authenticity, which are key to their full return to peaceful life.